Evaluating the effects of pelleting, corn dried distillers grains with solubles source, and supplementing sodium metabisulfite in nursery pig diets contaminated with deoxynivalenol - Frobose, H.L.; Hansen, E.L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 360 barrows (PIC 1050, initially 24.7 lb ± 0.3 lb BW and 35 d of age) were used in a 28-d trial examining the effects of pelleting, pelleting dried distillers grains with solubles (DDGS), and supplementing sodium metabisulfite4 (SMB) in diets containing deoxynivalenol (DON) on nursery pig performance. Pigs were allotted to 1 of 10 treatments with 7 replications per treatment (pens) and 5 pigs per pen. Naturally contaminated DDGS were used to incorporate DON at desired concentrations. Ingredients were tested for mycotoxins by the North Dakota State University Veterinary Diagnostic Laboratory (NDSU; Fargo, ND) and served as the basis for diet formulation. The 5 experimental diets were fed in meal and pellet form: (1) positive control, (2) negative control (NC, 5.3 ppm DON), (3) NC with 0.5% SMB, (4) pelleted and reground DDGS (5.3 ppm DON), and (5) pelleted and reground DDGS with 2.5% SMB (final diet contained 0.5% SMB). Experimental diets were fed from d 0 to 21 with a common diet fed from d 21 to 28 to evaluate performance after DON was removed. Due to the variability of DON assays when levels exceed 8 ppm, final diets were lower in DON than predicted from analysis of the DDGS. As a result, expected reductions in performance due to DON were not as significant as anticipated, and may have affected results. From d 0 to 21, pigs fed diets with high-DON levels had decreased (P < 0.03) ADG, but the reduction in ADG was only 4%. Pelleting high-DON diets decreased (P < 0.04) ADFI and improved (P < 0.02) F/G compared with diets fed in meal form; however, pelleting DDGS prior to manufacturing final diets had no effect on growth performance. Supplementing SMB tended (P < 0.08) to decrease ADFI, and had no effect on ADG or F/G. Our results indicate that pelleting high-DON nursery pig diets can recover some reduction in feed intake by improving F/G. Although pelleting DDGS and supplementing SMB did not improve performance in DON-contaminated diets, further studies are needed to verify these results.
Keywords: Swine; Deoxynivalenol; Pelleting; Sodium metabisulfite; Vomitoxin; Nursery pig